Corporate research & development investments international comparisons - Bhagat, Sanjai; Welch, Ivo (Journal of Accounting and Economics, 1995)
This paper explores the determinants of corporate R&D for U.S., Canadian, British, European, and Japanese firms. We find last year's debt ratio is significantly negatively correlated with current R&D expenditures for U.S. firms, and positively for Japanese firms. Second, we document a significant positive relation between two-year lagged stock return and current R&D expenditures for U.S., European, Japanese, and large-size British firms. Finally, we find a significant positive relation between last year's tax payments and current R&D expenditures for Japanese firms, and a significant negative relation for medium-size and small-size U.S. firms.